(3QSGdI aj JMbjb ShA GdeRGL eGgh hce CUfGags - (3YjSi Hf jMji GdeSjMj GdLQLGfj, CHh Sgd , J (B401 (3g` s
(3ChdgG (B:s
(3bGd CeQfi GdCejQ Cf CUfa cJGHkG CHMK ajg Yf ShA GdeRGL eGgh hce CUfGag heG MbjbI cd hGMO efgG aCbhd Cf LJg GdHOf TJed Ydi KdGKI CLfGS ef GdCLSGe GdWHjYjI s
(3BNQgG (B:s
(3hPdc Cf ShA eRGL GdYVh gh HYV CUfGa CeQGVg hGdPi hLH Cf fPcQ ai gPG GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B35s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs